Conditional RARα knockout mice reveal acute requirement for retinoic acid and RARα in homeostatic plasticity - Sarti, Federica; Schroeder, Jessica; Aoto, Jason; Chen, Lu (Frontiers in Molecular Neuroscience, 2012)
All-trans retinoic acid (RA) plays important roles in brain development through regulating gene transcription. Recently, a novel postdevelopmental role of RA in mature brain was proposed. Specifically, RA rapidly enhanced excitatory synaptic transmission independent of transcriptional regulation. RA synthesis was induced when excitatory synaptic transmission was chronically blocked, and RA then activated dendritic protein synthesis and synaptic insertion of homomeric GluA1 AMPA receptors, thereby compensating for the loss of neuronal activity in a homeostatic fashion. This action of RA was suggested to be mediated by its canonical receptor RARα but no genetic evidence was available. Thus, we here tested the fundamental requirement of RARα in homeostatic plasticity using conditional RARα knockout mice, and additionally performed a structure-function analysis of RARα. We show that acutely deleting RARα in neurons eliminated RA’s effect on excitatory synaptic transmission, and inhibited activity blockade-induced homeostatic synaptic plasticity. By expressing various RARα rescue constructs in RARα knockout neurons, we found that the DNA-binding domain of RARα was dispensable for its role in regulating synaptic strength, further supporting the notion that RA and RARα act in a non-transcriptional manner in this context. By contrast, the ligand-binding domain (LBD) and the mRNA-binding domain (F-domain) are both necessary and sufficient for the function of RARα in homeostatic plasticity. Furthermore, we found that homeostatic regulation performed by the LBD/F domains leads to insertion of calcium-permeable AMPA receptors. Our results confirm with unequivocal genetic approaches that RA and RARα perform essential non-transcriptional functions in regulating synaptic strength, and establish a functional link between the various domains of RARα and their involvement in regulating protein synthesis and excitatory synaptic transmission during homeostatic plasticity.